International Islamic Boarding School Strategy for Realizing Superior Islamic Boarding School Management - Efendi, Arief; Bueraheng, Ibroheng (IAIN Ponorogo, 2023)
This study aims to analyse the strategy of international Islamic boarding schools and the realization of continuous improvement in realizing superior Islamic boarding school management. This study employed qualitative research. The research describes various empirical phenomena implemented regarding excellent Islamic boarding school management at international Islamic boarding schools. The research setting was the Aqobah International School (AIS) Islamic boarding school, Jombang. The researchers analyzed the data using Miles Huberman's interactive analysis. The study results show that the strategy of international Islamic boarding schools in realizing superior Islamic boarding school management accepts all new students based on equality and equity. It believes that every child is special and can be a champion. Moreover, the management of students is based on data and research, standardization of the quality of teaching staff, standardization of infrastructure, and standardization of student personal service. As for the realization of continuous improvement in superior Islamic boarding school management ”“ integrating school and Islamic boarding school learning, specialization programs and checkpoint examination & IGCSE, and Cambridge curriculum.